Role of Cytokinins for Interactions of Plants With Microbial Pathogens and Pest Insects - Akhtar, Saqib Saleem; Mekureyaw, Mengistu F.; Pandey, Chandana; Roitsch, Thomas (Frontiers in Plant Science, 2020)
It has been recognized that cytokinins are plant hormones that influence not only numerous aspects of plant growth, development and physiology, including cell division, chloroplast differentiation and delay of senescence but the interaction with other organisms, including pathogens. Cytokinins are not only produced by plants but are also by other prokaryotic and eukaryotic organism such as bacteria, fungi, microalgae and insects. Notably, cytokinins are produced both by pathogenic and also beneficial microbes and are known to induce resistance in plants against pathogen infections. In this review the contrasting role of cytokinin for the defence and susceptibility of plants against bacterial and fungal pathogen and pest insects is assessed. We also discuss the cross talk of cytokinins with other phytohormones and the underlying mechanism involved in enhancing plant immunity against pathogen infections and explore possible practical applications in crop plant productionions.